Medical Students’ Knowledge, Attitudes, and Perceptions Toward Vaping and E-Cigarette Use: An Assessment of Their Education and Preparedness - Heather Hall; John Feest; Sydney Zarate; Martin S. Forde (International Medical Education, 2025)
The use of electronic cigarettes (e-cigarettes), or vaping, has risen significantly over the past decade as an alternative to traditional smoking. Despite growing evidence of vaping’s adverse health effects, limited data exist on medical students’ knowledge, attitudes, and behaviors regarding vaping, as well as the extent of education they receive on this topic. This study aimed to assess medical students’ perceptions of vaping-related harms and their evaluation of vaping education in medical school. A cross-sectional online survey was conducted among currently enrolled students at St. George’s University’s School of Medicine (n = 5794) over a five-week period from February to March 2024. The survey focused on students’ experiences, behaviors, attitudes, and perceptions toward e-cigarettes and vaping and their assessment of vaping-related education. Of 5794 invited students, 1400 (24%) responded, with 1193 (94%) completing the survey. While 82% had never used conventional tobacco cigarettes, 29% reported having vaped at least once. Nearly all respondents (97%) recognized vaping as a health risk; however, 75% reported receiving no formal education on vaping in their curriculum, and 68% rated their education on the topic as poor or very poor. Despite awareness of vaping’s risks, a notable proportion of medical students have engaged in the practice. The findings highlight a gap in medical education, underscoring the need for improved curriculum coverage to equip future physicians with the knowledge necessary to address vaping-related health concerns.